A Proposal of Critical Thresholds for Precipitation Triggering Mass Movement Processes. A Case Study: The State of Mexico - Valdés Fernández, Carlos Lázaro; Baró Suárez, José Emilio; Flores Olvera, Patricia; Franco Plata, Roberto (Revista Geográfica de América Central., 2022)
This research focuses on the study of precipitation triggering mass movement processes (MMP) to propose critical thresholds for early warning purposes in areas with the highest recurrence in the State of Mexico. An inventory of MMP was generated so that, once the events were located and the rain gauges were selected, the rain parameters to be plotted were recorded (daily and three-day accumulated rainfall, respectively). The inventory resulted in spotting 140 landslides, concentrated in three main areas of the state. A minimum threshold, a maximum threshold, and an intermediate threshold are proposed, based on daily and three-day accumulated rainfall values. These indicate a daily rainfall range between 52 and 105 millimeters capable of triggering some MMP in conditions of absent accumulated rain. On the other hand, a trend is observed in which the higher the accumulated rainfall values are, the lower the amount of daily rainfall to trigger an event of this type will be needed.